Ti3C2Tx MXene deposition: A simple surface engineering technique for dual enhancement of biological functions for nonbearing applications - Schickle, Karolina; Amousa, Nima; Pudelko, Iwona; Krok-Borkowicz, Malgorzata; Pamula, Elzbieta; Chlanda, Adrian; Romanowska, Agata; Kazek-Kesik, Alicja; Drozdz, Kamil; Gonzalez-Julian, Jesus; Justus Liebig University Giessen (My University, 2024)
Implant-associated complications, such as infection and poor osseointegration, present significant challenges in the field of biomedical implants. To address these issues, it is crucial to develop implant surfaces that possess both bacteriostatic and osteoconductive properties. In recent years, the field of surface modification for metallic substrates using two-dimensional materials has emerged as a highly promising strategy to enhance their biological properties. Among these materials, MXenes stand out as an excellent candidate for surface modifications due to their unique properties, such as biocompatibility, high specific surface area, and tunable chemical composition. In the present study, we introduce a simple deposition method of Ti3C2Tx MXene films on SS316L substrates to improve surface-cell interactions. The differentiation study demonstrated the alkaline phosphatase (ALP) enzyme activity on Ti3C2Tx-MXene-coated samples without osteogenic medium compared to uncoated samples in both, basic and osteogenic media. Moreover, the bacteriostatic character of the deposited MXene-coatings was confirmed against Gram-positive Staphylococcus aureus as well as Gram-negative Escherichia coli bacteria. The improved stimulation of both cell osteogenic differentiation and distinctive antimicrobial features triggered by Ti3C2Tx-MXene-coatings emphasizes their great potential as implant surface modifiers to improve integration and reduce the risk of infection in various biomedical applications.
Keywords: ddc:610